Maternal socio-demographic determinants and fetal outcome of intrauterine growth restriction - Singh, Arpita; K., Ambujam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Intrauterine Growth Restriction is a major neonatal health issue. It is associated with increased risk of perinatal morbidity and mortality. Maternal factors are the major contributing factors of IUGR and studying these factors can help in preventing IUGR and reducing perinatal mortality. The objective is to study the maternal sociodemographic risk factors associated with Intra uterine growth restriction. Methods: This is a Case-control study conducted in the Department of Obstetrics and Gynaecology, GMC Thrissur. 115 cases of Intra Uterine Growth Restriction were compared to 115 controls. Data was collected by interviewing the mother using structured questionnaire which is pretested and by persual of antenatal records. Intra Uterine Growth Restriction is defined as occurring if the sonographic estimated fetal weight <10th percentile for that gestational age. Chi Square test was used for the analysis of data. Results: Low socio-economic status and malnutrition (BMI<18.5) were significant socio-demographic factors associated with fetal growth restriction. Mean birth weight in IUGR group was 1.8kg compared to 2.9kg in control group. Female fetuses were more commonly associated with IUGR. Intra Uterine Growth Restricted babies had lower Apgar scores (<7) and had more chances for NICU admission. Conclusions: By studying the maternal risk factors associated with Intra Uterine Growth Restriction, we could identify the high-risk group. Early predictive studies could be done in these high-risk pregnancies with focus on good antenatal care to reduce the problem of IUGR in the community.